Ax+6=bx-4

Simple and best practice solution for Ax+6=bx-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Ax+6=bx-4 equation:


Simplifying
Ax + 6 = bx + -4

Reorder the terms:
6 + xA = bx + -4

Reorder the terms:
6 + xA = -4 + bx

Solving
6 + xA = -4 + bx

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1bx' to each side of the equation.
6 + -1bx + xA = -4 + bx + -1bx

Combine like terms: bx + -1bx = 0
6 + -1bx + xA = -4 + 0
6 + -1bx + xA = -4

Add '-6' to each side of the equation.
6 + -1bx + -6 + xA = -4 + -6

Reorder the terms:
6 + -6 + -1bx + xA = -4 + -6

Combine like terms: 6 + -6 = 0
0 + -1bx + xA = -4 + -6
-1bx + xA = -4 + -6

Combine like terms: -4 + -6 = -10
-1bx + xA = -10

Reorder the terms:
10 + -1bx + xA = -10 + 10

Combine like terms: -10 + 10 = 0
10 + -1bx + xA = 0

The solution to this equation could not be determined.

See similar equations:

| -6(w+9)=2w+10 | | 16-5x=3(x-8) | | x^2-12x+40=-x^2+12x-24 | | x*y=6.49 | | 2x=(360/ | | 2x*(4)-3+x*7.45=3x-4/9 | | 1300/2600 | | I-I=0 | | Y=2(2a+4b)fora | | (K-3)2=121 | | 8(x-1)-2= | | 2i-3i/8=75.4 | | 60x^2-28xy+20x= | | 2i-2i=1 | | X^2+.08x+.024=0 | | (x-7)-(x-9)= | | 2/3=1/3c | | (3x-5)(9x-7)=0 | | N=.18 | | 2x/(7x-8)-x=5x | | (x*x)+5x+(y*y)-3y=0 | | 3(x-1)2-4=5 | | 15=3x-36 | | 4x/10-5=4 | | cos(x)-xsin(x)=0 | | 1.3-6x=-27.4-1.9x | | (25b-7)-8(3b+1)=-3 | | 3s+5l=410 | | 36+3(4x-9)=y(2x+1)+25 | | 10x+4y+6z+-5x+3z-7= | | l=s+26 | | In(x+9)+IN(x+1)=In(4) |

Equations solver categories